PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM UPAYA MENINGKATKAN KINERJA GURU : (Studi Kasus Di SMPS Barunawati Surabaya) - Istijarti, Atiek (Universitas Negeri Surabaya, 2023)
The leadership type of a school principal has a significant role in improving teacher performance and the learning process in schools. This study aims to find out how the principal's leadership type influences the performance of SMPS Barunawati Surabaya teachers. This study uses a qualitative descriptive approach with data collection methods through observation, interviews and documentation. The data obtained were tested for credibility, transferability, dependability and confirmability. The results of the study show that the principal's leadership in efforts to improve teacher performance in generally good. Teacher performance at SMPS Barunawati Surabaya was observed based on teacher competence. Principal leadership is democratic and has made efforts to improve teacher competency through improving pedagogic, personality, social, professional, discipline, providing motivation, organizing and completing infrastructure, giving appropriate assignments and awards to teachers. This type of principal leadership can increase the commitment and skills of teachers in carrying out their duties.